The search for meaning and the illusion of escaping - Osmanović, Sabina (Primerjalna književnost, 2020)
This paper is an analysis of Martin Walser's novella Runaway Horse (1977) about the midlife crisis. It describes the search for meaning of a man in his mid-fifties, his imprisonment in futility and the illusion of a possible flight from this abyss. With this novella Walser embarked on the broad field of philosophy, the ambiguity of postmodern existence and the questioning of traditional lifestyles. In addition, Walser is one of the first writers to artistically address the challenges and crises of age - especially in times of demographic change and the "aging of society", a highly controversial topic. The question that runs through Walser's novella is: how to live and how to love? Walser does not offer simple answers to all these questions, but he exacerbates the problems that we perceive only vaguely in our everyday life, at the highest level in literature and philosophy. That is why Walser's characters appear so credible and why Runaway Horse represents a palpable example of the expressive power of literature.
Keywords: iskanje smisla; kriza srednjih let; nemška književnost; Walser, Martin